HUBUNGAN INTENSITAS MENDENGARKAN CERAMAH, PEMAHAMAN BUKU TEKS DAN PARTISIPASI BERORGANISASI DENGAN RETORIKA - Haryadi Haryadi (Jurnal Kependidikan, 2003)
Abstract The purpose of this study is to determine a correlation between lecture listening intensity, textbook reading comprehension, in organization participation and rhetoric. The survey was conducted at Yogyakarta Islamic High School, and the sample was 100 students selected by simple random sampling. The study reveals that there are positive correlation between lecturer listening intensity and rhetoric, textbook reading comprehension with rhetoric, in organization participation and rhetoric, and furthermore, there is positive correlation between those three independent variables and rhetoric. Keywords: rhetoric, listening intensity, textbook reading comprehension, organization participation